Star formation, metallicity gradient and ionized gas : clues to the formation of the elliptical galaxies NGC 6868 and 5903 - Rickes, Mauro Cristian Garcia (2008)
The stellar population, metallicity distribution and ionized gas in the elliptical galaxies NGC6868 and 5903 are investigated in this paper by means of long-slit spectroscopy and stellar population synthesis. Lick indices in both galaxies present a negative gradient indicating an overabundance of Fe, Mg, Na and TiO in the central parts with respect to the external regions. We found that Mg2 correlates both with Fe I λ5270 and Fe I λ5335, suggesting that these elements probably underwent the same enrichment process in NGC 6868. However, only a marginal correlation of Mg2 and Fe I λ5270 occurs in NGC5903. The lack of correlation between computed galaxy mass and the Mg2 gradient suggests that these elliptical galaxies were formed by merger events. The stellar population synthesis shows the presence of at least two populations with ages of 13 and 5 Gyr old in both galaxies. We have estimated the metallicity of the galaxies using single-aged stellar population (SSP) models. The central region of NGC6868 (|R| 0.5 < ~ kpc) presents a deficiency of alpha elements with respect to iron and solar metallicity. The external parts present a roughly uniform distribution of [α/Fe] ratios and metallicities ranging from [Z/Zʘ] = − 0.33 and solar. A similar conclusion applies to NGC5903. Concerning the emitting gas conspicuously detected in NGC6868, we test three hypotheses as ionizing source: an H II region, post-AGB (asymptotic giant branch) stars and an active galactic nucleus (AGN). Diagnostic diagrams involving the ratios ([N II] λ6584)/(Hα), ([O I] λ6300)/(Hα) and ([S II] λλ6717, 6731)/(Hα) indicate that values measured in the central region of NGC6868 are typical of LINERs (Low-Ionization Nuclear Emission-Line Regions). Together with the stellar population synthesis, this result suggests that the main source of gas ionization in NGC6868 is non-thermal, produced by a low-luminosity AGN, probably with some contribution of shocks to explain ionization at distances of ~ 3.5 kpc from the nucleus.